Energy efficient resource management techniques in cloud environment for web-based community by machine learning: a survey. (15th August 2019) - Pandey, Pratibha; Singh, Abhishek
Cloud computing is a platform where the services of information technology are delivered by retrieval of resource from the internet through web applications and web tools instead of using direct server. In order to offer better quality of service to the larger number of web-based community users, many companies are adopting cloud computing. A dynamic number of web-based community user are interacting with each other via cloud computing. The number of online users is not just limited to manual counting figure so it is extremely important to manage each and every resource efficiently by minimising the energy consumption. To increase the performance of the system, the concepts of machine learning can be used to solve the challenges occur in cloud computing while managing resources for online communities. In this paper, we discuss the application of machine learning in cloud environment and its effect on web-based community.